The Impact of Innovation Activities, Foreign Direct Investment on Improved Green Productivity: Evidence From Developing Countries - Xu, Sa; Li, Zejun (Frontiers in Environmental Science, 2021)
This study, based on global Malmquist-Luenberger productivity index, introduces an improved green productivity (IGP) index to measure the green productivity change in16 developing countries from 1991 to 2014. In particular, we examine the impact of innovation activities and foreign direct investment (FDI) on IGP. The results indicate that IGP in developing countries have declined. Innovation activities have a pcositive impact on IGP while FDI has a significant negative impact on IGP. Dividing the sample countries into BRICS and non-BRICS countries yield some different results. We also find threshold effects between FDI and IGP based on innovation activities. Policy implications of the findings are discussed.